2017
DOI: 10.1002/cncr.30689
|View full text |Cite
|
Sign up to set email alerts
|

Insurance denials for cancer clinical trial participation after the Affordable Care Act mandate

Abstract: Despite the ACA's mandate for most insurers to cover routine care costs for cancer clinical trial participation, denials and delays continue. Denials may continue because some insurers remain exempt from the law, or they may signal an implementation failure. Delays in coverage may affect patient participation in trials. Additional efforts to eliminate this barrier will be needed to achieve federal initiatives to double the pace of cancer research over the next 5 years. Future work should assess the law's effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…On the basis of data from a single clinical center, the percentage of health insurance clearance for patients with cancer who were being considered for clinical trials during 2012 through 2015 increased, and the likelihood of prolonged clearance lowered, after the clinical trial coverage provision in 2014 105 . However, another study using data from 252 cancer research centers and community‐based institutions showed that insurance denials and delays continued after the ACA provision 106 …”
Section: Overview Of Research Addressing the Aca And Cancer Carementioning
confidence: 99%
“…On the basis of data from a single clinical center, the percentage of health insurance clearance for patients with cancer who were being considered for clinical trials during 2012 through 2015 increased, and the likelihood of prolonged clearance lowered, after the clinical trial coverage provision in 2014 105 . However, another study using data from 252 cancer research centers and community‐based institutions showed that insurance denials and delays continued after the ACA provision 106 …”
Section: Overview Of Research Addressing the Aca And Cancer Carementioning
confidence: 99%
“…Grandfathered plans, out-of-network providers/sites, and claims by insurers that they did not cover clinical trials were the most common reasons for denial of coverage. 46 (Table 3). Some states cover only specific phases of oncology clinical trials.…”
Section: Medicaid and Oncology Clinical Trial Coveragementioning
confidence: 99%
“…Perhaps the most distressing drawback of current genomic profiling techniques is a lack of concordance between clinical-grade laboratories. The same patient sample, if sent to multiple Clinical Laboratory Improvement Amendments (CLIA)-licensed laboratories for sequencing, will often yield disparate results 22 . Practically speaking, a patient’s clinical care may differ based only on the molecular pathology group that performed the genomic profiling.…”
mentioning
confidence: 99%
“…Practically speaking, a patient’s clinical care may differ based only on the molecular pathology group that performed the genomic profiling. This inconsistency may lead to poorly informed clinical decisions, inappropriate clinical trial enrollment, and skewed interpretations of efficacy for targeted therapies being investigated in molecularly-inspired clinical trials 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation